Caracterização geotécnica e análise do comportamento de aterros sobre solos moles para a construção do novo acesso ao complexo de Suape - Melo, Mário Paulo Barros (2011)
This paper presents the geotechnical investigation, critical analysis of design and performance of embankments on soft soils for the construction of new access to ZIP - Port Industrial Zone in SUAPE. This research is very important because it is a study of soil in an area with little information and geotechnical huge potential for development. The work presents an extension of 4.254 km, the project includes construction of landfills in two stages, with the placement of geodrenos, blanket application of geotextiles, drainage mat, placement of geosynthetics and temporary overload. The objective of this research work is to conduct a study of the soil layer at the scene, and make a critical analysis of design and monitoring of vertical displacements and pore pressures. From the results, it was observed that there is a thick layer of soft soil, with variations in the thickness of four pieces of work. It was found, in general, that the settlements are higher than estimated by the paper and the measured lower than envisaged in the project. It is noteworthy that the instrumentation was installed at the end of the first phase of construction, which complicates the interpretation of the readings. It was also seen in the analysis of project, the number adopted as the compression rate is acceptable to the prediction of repression. Note also that differential repression occurred in the longitudinal and transverse directions in all parts of the work